The Assessment of Response to Adjuvant Chemotherapy with CMF in Triple Negative Breast Cancer - Seyyed Asadolah Mousavi; Efat Mashhadi; Masud Iravani; Ardeshir Ghavamzade (International Journal of Hematology-Oncology and Stem Cell Research, 2013)
Introduction: Breast cancers are divided into at least 4 sub Types on the Basis of gene expression profiles and expression of receptors as measured by IHC (Immunohistochemical). Triple negative breast cancer (TNBC) is more chemosensitive yet, it is much harder to detect than other sub types. At present lack of highly effective therapeutic targets for TNBC, Leaves standard chemotherapy, as the only medical treatment but it is not remarkably efficient. CMF (cyclophosphamide-MTX-5-fu) chemotherapy is effective in some sub types of TNBC. Patients and methods: A Total of 40 patients with TNBC who had undergone surgical resection because of primary Invasive Breast cancer were studied from 2009 to 2011. Twenty patients in treatment group received four cycles of modified CMF after standard chemotherapy and 20 patients in group control Received standard chemotherapy (Antracycline / Taxane), Patients were Regularly Followed up every 3 months for median observation 13.3 mo. Results: In our study the prevalence of TNBC w s %13.5 The average age of patients 49.5 years Their clinical and histopathological characteristics include: 90% Invasive Ductal carcinoma, 55.35% LN(Lymph node) pos. 61.3% P53 Pos , 74.5% Ki67  20 , 68% grade III. There was No statistical differenced between control and treatment group in OS, DFS and PD median Followed up 13.3 mo. Conclusion: The results of study indicate that the adjuvant therapy with regimen CMF in TNBC patient after standard chemotherapy with Antracyline / Taxane- Base no affected out come in patient in Median follow up 13.3 mo.